The international religious freedom act 1998 and the role of religious movement - Mohd Afandi Salleh (Penerbit UKM, 2011)
The introduction of the International Religious Freedom Act (IRFA) in October 1998 creates a new landscape of international law where religion became a central issue. In addition, the Act establishes a new dimension in the U.S. foreign relations when it considers global religious freedom as an important concern of its foreign affairs. The objective of this article is to study the role of American Evangelicals in U.S. foreign policy making with regards to the IRFA. It thus examine three major issues, firstly the constellation of interests of American evangelicals on the issue of global religious freedom and their contributions to the passage of the International Religious Freedom Act. Secondly, it highlights briefly the contents of the IRFA and its impact to the US foreign relations with other countries particularly Muslim countries. Finally it critically examines the execution of that Act during George W. Bush administration. The article found that, though American evangelicals were significantly contributed to the passage of the Act, they had no control or influence over the implementation of IRFA in U.S. foreign policy.